REFLEXE ZÁŽITKOVÉ PEDAGOGIKY V PEDAGOGICE A KINANTROPOLOGII [REFLECTION OF EXPERIENTIAL PEDAGOGY IN PEDAGOGOGY AND KINATHROPOLOGY] - Petr Zappe (Palacký University Olomouc, 2009)
Přestože pojem zážitková pedagogika na první pohled odkazuje k pedagogice, má dnes tato oblast užší a jasnější vztahy s kinantropologií než s pedagogickými vědami. Příčiny tohoto stavu je vhodné hledat ve vývoji pedagogiky po listopadové revoluci. Pedagogika prožila bouřlivý rozvoj, ve kterém se zaměřovala převážně na školskou pedagogiku a vznik mladých disciplín v jiných oblastech nestíhala sledovat. Jedním z dlouho nereflektovaných problémů pedagogiky bylo samo pojetí výchovy. Současný pohled na tento fenomén sbližuje pedagogiku a zážitkovou pedagogiku. [Experiential pedagogy seems to be referencing pedagogy. But in fact it has established closer and better relationship with kinanthropology. I find it meaningful to search for causes of this situation in the development of pedagogy after the velvet revolution. This development was turbulent. pedagogy focused mainly on school education and it was not able to follow formation of jung disciplines in other areas. One of the missed out problematic points was the conception of education itself. Contemporary way of understanding it converges pedagogy and experiential pedagogy.]